2011
DOI: 10.1007/s00420-011-0655-2
|View full text |Cite
|
Sign up to set email alerts
|

An updated historical cohort mortality study of workers exposed to asbestos in a refitting shipyard, 1947–2007

Abstract: This updated study confirmed a significant excess of asbestos-related mortality from diseases such as lung cancer and nonmalignant respiratory diseases among workers in a refitting shipyard in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…A flow chart of literature search and study selection process is presented in supplementary files (http://onlinelibrary.wiley.com/doi/10.1111/dote.12341/suppinfo). Totally, 20 independent cohort studies were collected in this meta‐analysis. One study reported findings from two distinct cohorts, and thus we analyzed data on 21 distinct populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A flow chart of literature search and study selection process is presented in supplementary files (http://onlinelibrary.wiley.com/doi/10.1111/dote.12341/suppinfo). Totally, 20 independent cohort studies were collected in this meta‐analysis. One study reported findings from two distinct cohorts, and thus we analyzed data on 21 distinct populations.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were conducted in Asia, seven in Europe, four in United States and three in Oceania. Five studies were conducted only in male cohort, and one cohort included only female. The industries involved mining, textiles, refitting shipyard, reprocessing plant, and others.…”
Section: Resultsmentioning
confidence: 99%
“…Shipyards are well-known emitters of asbestos (Beckett 2007;Hollins et al 2009;Tomioka et al 2011), a substance recognized by the IARC as a lung carcinogen in humans (IARC 2012). In this connection, Barbone et al found an excess risk of lung adenocarcinoma in the proximity of a shipyard in Trieste, Italy (Barbone et al 1995), and Bianchi et al stated that asbestos exposure may reach alarming levels in shipyard areas (Bianchi et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were performed in Europe, five in Asia (Wang et al 2013;Du et al 2012;Tomioka et al 2011;Sun et al 2003;Kurumatani et al 1999), three in America (Loomis et al 2009;Hein et al 2007;and Tsai et al 1996), and four in Oceania Reid et al 2008Reid et al , 2004and Armstrong et al 1988). Thirteen studies Menegozzo et al 2011;Tomioka et al 2011;Pesch et al 2010;Pira et al 2009;Kjaerheim et al 2005;Reid et al 2004;Szeszenia-Dabrowska et al 2002;Battista et al 1999;Kurumatani et al 1999;Kurumatani et al 1999;Raffn et al 1989;and Armstrong et al 1988) were conducted only in male cohort, and five cohorts (Reid et al 2004;Sun et al 2003;Germani et al 1999;Magnani et al 2008;and Acheson et al 1982) included only female. The main type of industries included refitting shipyard, mining, textile, and cement.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…We carefully reviewed the abstracts or full texts of these papers. Totally, forty cohorts from 32 independent studies (Harding et al 2009;Musk et al 2008;Wang et al 2013;Du et al 2012;Menegozzo et al 2011;Tomioka et al 2011;Pesch et al 2010;Clin et al 2009;Loomis et al 2009;Pira et al 2009;Frost et al 2008;Reid et al 2008;Hein et al 2007;Kjaerheim et al 2005;Pira et al 2005;Wilczyńska et al 2005;Reid et al 2004;Smailyte et al 2004;Sun et al 2003;de La Provôté et al 2002;Szeszenia-Dabrowska et al 2002;Berry et al 2000;Battista et al 1999;Germani et al 1999;Kurumatani et al 1999;Tsai et al 1996;Dement et al 1994;Tarchi et al 1994;Magnani et al 2008;Raffn et al 1989;Armstrong et al 1988;Acheson et al 1982) met the criteria for inclusion in the meta-analysis. Table 1 summarized all the available cohort studies with acknowledged asbestos exposure, which we have been able to identify.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%